Improving visibility of public libraries in the local community: A study of five public libraries in Zagreb, Croatia - Vrana, Radovan; Barbarić, Ana (2007)
The purpose of this paper is to establish whether or not promotional efforts can help public libraries to become more visible and their services more recognizable in the local community. At present, libraries employ different promotional efforts for their products and services, usually less aggressive than commercial information providers. Their final goal is to reclaim the role of the primary provider of quality information resources and accompanying services from electronic media.
Projekt MZOS
ENG